Implementasi Metode Drill untuk Peningkatan Kemampuan Siswa Memahami Kaidah Nahwu pada Siswa Kelas VII B MTs Nurul Hidayah Simpang Asahan Tulang Bawang Barat - Subiantoro Subiantoro (Jurnal Ilmiah Wahana Pendidikan, 2021)
This study aims to: (1) determine the implementation of the drill method to improve students' ability to understand the rules of nahwu in class VII B MTs Nurul Hidayah Al Amin Simpang Asahan. (2) find out how effective the implementation of the drill method is to increase students' ability to understand the rules of nahwu in class VII B students of MTs Nurul Hidayah. This research is qualitative, the research location is at MTs Nurul Hidayah Simpang Asahan for the 2020/2021 academic year. This type of research is Classroom Action Research (CAR). The research subjects were students of class VII B MTs Nurul Hidayah with a total of 22 students consisting of 10 students and 12 students. Collecting data using observation sheets, documentation, as well as pre-test, post-test and evaluation questions. The data analysis stage is carried out by collecting data first and then analyzing it with theories and concepts that are general in nature and related to facts to investigate the issue. The stages of research activities include planning (planing), action (action), observation (observing), and reflection (reflecting). The results of this study indicate two main conclusions: (1) the implementation of this classroom action research activity was carried out in two cycles, each cycle consisting of three meetings. (2) after the implementation of the drill method and supported by varied models of exercises in learning Arabic , the ability of students to understand the rules of nahwu has increased. It is known from the results of the class average of the pre test, post test, and evaluation in the first cycle from 20.57 to 45.12 and 32.05. While in the second cycle the average value of pre-test, post-test, and evaluation increased from 21.47 to 43.9 and 59.3. From the increase in students obtained, the researchers stated that the implementation of the drill method and supported by varied media and exercises so that students did not feel bored and rigid in learning was very effective in increasing students' ability to understand the rules of nahwu.